APRUMO (Agile Process Modeling) - A Method to Process Modeling Using Agile BPM - Lohmann, Pedro Alfradique; Vieira, Caio Sarmento Marinho; Magdaleno, Andrea Magalhães; Engiel, Priscila (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Agile BPM is the integration and adaptation of agile practices, deriving from the software development to the BPM (Business Process Management) cycle as an alternative to the traditional BPM approach. Agile BPM recommends iterative process management, with continuous delivery, customer approximation through validations and information sharing, turning the BPM evolution more visible and resulting in suitable modeling to specific customer needs. The proposal of this paper consists of the definition of APRUMO (Agile Process Modelling) where Agile BPM concepts are applied in the business process modeling phase. The method is organized in phases and with roles and responsibilities defined. A case study was planned and conducted in a real company for 5 months and involved 5 professionals of the company. At the end of the study, 2 sprints and 10 meetings were performed, delivering 7 process models. A questionnaire answered by participants showed that simplicity and flexibility were positive points and, on the other hand, they needed extra working time on it. This study demonstrated the method’s agile practices viability, resulting in participative customer and improved information extraction during the gathering process. It was also possible to identify some difficulties to apply APRUMO such as the need for a process team with modeling experience, the need of customer engagement and other as the need for complementary documents to produced models.